Contributions of physical activity in the aging of the elderly - Guerra, Maria de Fátima Santana de Souza (2021)
The characteristic of aging does not depend only on the genetic condition, but above all, on the lifestyle. Therefore, in order to understand the etiology associated with the degenerative processes associated with it, it is essential to know and develop strategies that mitigate the effects of senescence and senility. Therefore, the study aims to analyze the influence of physical activity on the social aspect of the elderly through a bibliographic survey. The methodology used was narrative review, using online databases as reliable sites; electronic magazines; books; newspapers. The data collection was not restricted to the year of publication of the works found. In the search for data, the works that contemplated the theme in question were chosen, making use of a previous reading of the titles; abstracts or prologue or introductory text depending on the type of publication; finally the reading of the entire text. The results reveal that the insertion of an active lifestyle, through the practice of physical activity, provides biopsychosocial and spiritual benefits to the health of the elderly, since it is considered as an important component to improve the quality of life and their independence functional. Thus, from this literature review, it is concluded that the physical activity method contributes positively to the healthy aging of the elderly and that, due to the increase in longevity and the progressive decrease in the birth rate, this population will increase in the coming years.